Pengaruh Pemasaran Digital, Citra Merek, dan Gaya Hidup Terhadap Keputusan Pembelian dalam Memilih Coffee Shop di Yogyakarta - Nasa Nurul Ubay (Institut Nalanda, 2023)
The coffee industry in Indonesia is experiencing significant growth and making an important contribution to national economic growth. During the period 2016-2021, coffee consumption in Indonesia is estimated to grow at an average of 8.22% per year, and in 2021, coffee supply is estimated to reach 795 thousand tons, with consumption of 370 thousand tons, causing a surplus of around 425 thousand tons. This has led to the rise of the coffee shop business in Indonesia, causing the coffee-based market competition to be very tight, requiring coffee shops to provide something different to win this competition. This study aims to determine the effect of digital marketing, brand image and lifestyle on purchasing decisions in choosing a coffee shop in Yogyakarta. The population used in this study are consumers who often visit various coffee shops in Yogyakarta. The data used is primary data with 250 respondents. The data collection technique uses non probability sampling with convenience sampling method and is applied in google form. Analysis using the SEM method and processed using the Smart-PLS application. The results of this study indicate that of the three hypotheses have a positive effect and two hypotheses have no positive effect